Ageing and intergenerational relations : family reciprocity from a global perspective - Izuhara, Misa. (Bristol : Policy Press, 2010)
"With socio-economic and demographic changes taking place in contemporary societies, new patterns of family relations are forming partly due to significant family changes, value shifts, precariousness in the labour market, and increasing mobility within and beyond national boundaries. This exciting book explores the exchange of support between generations and examines variations in contemporary practices and rationales in different regions and societies around the world. It draws on theoretical perspectives and empirical analyses to discuss both newly emerging patterns of family reciprocity and more established ones which are affected by changing opportunities and pressures in contemporary societies. The book is split into two parts: the first reviews key theoretical and conceptual debates in this field, while the second offers new insights and an understanding of exchange practices based on case studies from different regions and different relationships."--Publisher's description.
HKBU library
YT2025 M10
Keywords: Aging; Intergenerational relations; Older people -- Social conditions